2019
DOI: 10.1111/tpj.14266
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis of the early steps in strigolactone‐mediated axillary bud dormancy in rice

Abstract: SummaryBy contrast with rapid progress in understanding the mechanisms of biosynthesis and signaling of strigolactone (SL), mechanisms by which SL inhibits axillary bud outgrowth are less well understood. We established a rice (Oryza sativa L.) hydroponic culture system to observe axillary buds at the critical point when the buds enter the dormant state. In situ hybridization analysis indicated that cell division stops in the leaf primordia of the buds entering dormancy. We compared transcriptomes in the axill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 100 publications
1
44
0
Order By: Relevance
“…For instance, both SL and GA can affect internode elongation by stimulating cell division, but SL works independently of the GA signal in this process [177]. In addition, the roles of SL and GA in branch regulation are independent in pea [178]. GA 3 could significantly increase seed germination of kai2 and max2 mutants, indicating that KAI2 and MAX2 may not be involved in the stimulation of GA on seed germination [63].…”
Section: Sl or Kar Crosstalk With Gibberellinmentioning
confidence: 99%
“…For instance, both SL and GA can affect internode elongation by stimulating cell division, but SL works independently of the GA signal in this process [177]. In addition, the roles of SL and GA in branch regulation are independent in pea [178]. GA 3 could significantly increase seed germination of kai2 and max2 mutants, indicating that KAI2 and MAX2 may not be involved in the stimulation of GA on seed germination [63].…”
Section: Sl or Kar Crosstalk With Gibberellinmentioning
confidence: 99%
“…In addition, genes involved in ABA biosynthesis and signalling were highly expressed in the axillary buds under HN, especially 5.0 mM N. A previous study revealed that the signalling regulators of ABA play roles in the response to ammonium toxicity [68], indicating that ABA should be involved in the axillary bud growth of plants under different N concentrations. Luo et al (2019) recently proposed that ABA suppresses the axillary bud growth of SL mutants and regulates SL-mediated axillary bud dormancy [69], suggesting that ABA may be involved in axillary bud dormancy to inhibit the bud outgrowth of plants under LN conditions. Genes related to the biosynthesis and degradation of GA were expressed at high and low levels, respectively, in the axillary buds under LN conditions.…”
Section: Phytohormones Involved In the Axillary Bud Growth Of Plants mentioning
confidence: 99%
“…Beyond this specific question the work presented by Luo et al . (), provides a highly important example of how hormone function contributes to the control of normal growth. Such insight is lacking not just for strigolactones but also for most other phytohormones.…”
mentioning
confidence: 99%
“…Furthermore, evaluation of the transcriptomic data revealed that several ABA responsive genes as well as genes associated to ABA biosynthesis were induced on the transition to dormancy. Given this observation Luo et al (2019) next tested whether ABA suppresses bud outgrowth in rice by adding low concentrations of ABA which do not invoke major changes in plant growth. Intriguingly, while this addition of ABA did not affect tiller bud growth in wild-type plants it suppressed the growth of tiller buds in the strigolactone-deficient d10-1 mutant via an effect on cell division as well as their growth in the strigolactone signaling mutant d14-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation